Constructing hierarchical spheres from large ultrathin anatase TiO2 nanosheets with nearly 100% exposed (001) facets for fast reversible lithium storage - Chen, Jun Song (2012)
Synthesis of nanocrystals with exposed high-energy facets is a well-known challenge in many fields of science and technology. The higher reactivity of these facets simultaneously makes them desirable catalysts for sluggish chemical reactions and leads to their small populations in an equilibrated crystal. Using anatase TiO2 as an example, we demonstrate a facile approach for creating high-surface-area stable nanosheets comprising nearly 100% exposed (001) facets. Our approach relies on spontaneous assembly of the nanosheets into three-dimensional hierarchical spheres, which stabilizes them from collapse. We show that the high surface density of exposed TiO2 (001) facets leads to fast lithium insertion/deinsertion processes in batteries that mimic features seen in high-power electrochemical capacitors.